Infecção nosocomial da corrente sanguínea por Staphy- lococcus aureus: avaliação do tempo de permanência, mor- talidade atribuída e custos diretos extras - PRIMO, Mariusa Gomes Borges (2006)
Objective: To determine the excess length of stay extra costs and mortality attributable to nosocomial S aureus bloodstream infection at a teaching hospital in Goiânia-Goiás Methods: Pairwise-matched (1:1) case-control study All patients older than 13 years admitted at the University Hospital of UFG between 2000 and 2001 were eligible Cases were defined as patients with a nosocomial S aureus bacteremia and controls were patients without bacteremia matched by gender age (+7 years) primary diagnosis and underlying diseases using the International Classification of Disease codes (CID-10) yielding 84 matched case-control pairs Data were collected from medical records and from the Brazilian National Hospital Information System (SIH/SUS) Descriptive and analytic statistics were performed. Wilcoxon rank sum test was performed to compare length of stay and costs between the cases and controls Mortality among cases and controls was compared using McNemar s test (EpiInfo 6.0 and SPSS/PC 13.0) The study protocol was approved by the Ethical Committee. Results: Cases and controls were similar regarding age and gender with a slight male predominance McCabe severity of illness scores revealed that approximately 40.0% of all patients had fatal or rapidly fatal illness without difference among cases and controls The mean length of total hospital stay for cases was 48.3 days versus a mean for controls of 16.2 days (p< .01) yielding an excess of hospital stay of 32.1 days Forty-eight of the 84 cases died representing a crude mortality rate of 57.1% For controls the crude mortality rate was 11.9% The attributable mortality rate was estimated to be 45.2% Cases had a 7.3 fold higher risk for death than controls (OR= 7.3; IC95% 3.1-21.1) Overall costs of hospitalization (SIS/SUS) reached R$ 290.434 for cases versus R$ 94.982 for controls (p< .01) Antimicrobial therapy cost was 6.7 fold higher for cases compared to controls Conclusion: Nosocomial bloodstream infection caused by S aureus was associated with significant increases in length of hospitalization attributable mortality and economic burden at a teaching hospital Measures to minimize the risk of nosocomial bloodstream infection are essential